METHODS OF ACTIVE STUDY OF MATHEMATICAL DISCIPLINES IN HIGHER EDUCATION - Skorokhod Г.І.; Lamzyuk В.Д. (Pedagogy of Higher and Secondary Education, 2022)
We considered methods of developing teaching and active gaming in mathematical courses at higher education institutions: problem-solving training, heuristic methods, a didactic elements enlargement, task types for active learning.